The future orientation for novice teacher induction program in vocational education - Pramudi Utomo (Jurnal Pendidikan Vokasi, 2018)
This paper presents the discussion with purpose to identify the orientation of teacher induction program in vocational education that is in line with changing times and future challenges. The problems associated with the teacher induction program in vocational education are whether the program has been oriented towards changes and future challenges. This research was conducted explanatory sequential mixed method approach. This study applies a six-step on research procedure. Respondents consisted of 52 novice teachers, 115 mentors, 15 principals, and 24 school supervisors. The subject of the qualitative research was nine resources persons. The respondents were given a Likert scale questionnaire to gather opinions and to be interviewed about the implementation of induction programs in vocational schools. Data were analyzed using PASW-18 and Atlas.ti software. The results of the study indicate that the future orientation of the induction program for novice vocational teachers involves many aspects in teacher professional development. These aspects include understanding of new target groups, developing job markets, technological developments, business/industry cooperation, regional development, new learning paradigms, and vocational education policy.